A tale of two dialect regions Sranan's 17th-century English input - Sherriah, André (Language Science Press, 2019)
This book traces the precise origin of the early English lexical and lexico-phonetic influences in Sranan, an English-based creole spoken in Suriname. Sranan contains "fossilised" linguistic remnants of an early English colonial period. The book discusses whether Sranan's English influence(s) originated from a single dialect from the general London area, as proposed by Norval Smith in 1987, or whether we are dealing with a composite of dialectal features from all over England. The book introduces a novel replicable methodology for linguistic reconstructions, which combines statistics (in the form of binomial probability), English dialect geography (via use of Orton's et. al., 1962-1971, Survey of English Dialects, which focuses on traditional regional English dialects across England and Wales), and 17th-century English migration history.